Effect of Single Shot Intrathecal Sufentanil on Delivery Time and Analgesia in Nuliparae - Ebrahim Khoshraftar (پزشکی بالینی ابن سینا, 2008)
Introduction & Objective: The objective of this study was to determine the evaluation of intrathecal sufentanil for labor analgesia with respect to duration of labor stages and relief of pain during labor.